Interaksi Sosial antar Pemeluk Agama di Madinah Era Nabi Muhammad Saw Perspektif Kajian Hadis - Landy Trisna Abdurrahman (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2021)
The interaction between human beings, regardless of the differences, is a necessity. Also interaction and intercommunication between religious communities is no exception in this contemporary era. However, there are various narratives that are quite discriminatory in Islam which can be used as a basis for discriminating against and hating followers of other religions. Whereas in the early era of Islam, especially in the era of Medina, the Prophet Muhammad (PBUH) had interacted with followers of other religions, especially Jews, Christians, Magi (majusi), and Pagans. Even Medina before the Prophet's era was a fairly plural area in terms of belief and religion. This paper is written by asking questions (1) how was the social interaction at the beginning of the Prophet Muhammad in Medina from the perspective of hadith, and (2) what is the “basic idea” contained in the hadith narrations that recorded social interactions in Medina during the era of the Prophet Muhammad? The results of the research in this paper found that there were social interactions between religious communities that were quite intense and in the principle of helping each other and obeying the Prophet Muhammad as a leader. The basic idea in the hadith narrations that record social interactions at that time is that the Prophet Muhammad SAW punished or attacked people of other religions because of their disobedience and disobedience, not solely because of their beliefs.[Interaksi antar umat manusia, apapun perbedaannya, adalah hal yang niscaya. Tak terkecuali interaksi antar umat beragama di era kontemporer ini. Namun terdapat berbagai narasi yang cukup diskriminatif dalam agama Islam yang bisa dijadikan dasar untuk bertindak diskriminatif dan membenci pemeluk agama lain. Padahal pada era awal Islam, terutama pada era Madinah, Nabi Muhammad SAW telah berinteraksi dengan umat pemeluk agama lain, terutama Yahudi, Nasrani, Majusi, dan kaum Pagans. Bahkan Madinah sebelum era Nabi adalah daerah yang cukup plural dari sisi kepercayaan dan agama. Makalah ini ditulis dengan mengajukan pertanyaan (1) bagaimana interaksi sosial pada masa awal Nabi Muhammad di Madinah dalam perspektif hadis, serta (2) ide dasar apa yang terkandung dalam riwayat-riwayat hadis yang merekam interaksi sosial di Madinah pada era Nabi Muhammad SAW? Hasil penelitian dalam makalah ini menemukan bahwa terdapat interaksi sosial antar umat beragama yang cukup intens dan dalam prinsip saling membantu serta menaati Nabi Muhammad sebagai seorang pemimpin. Ide dasar pada riwayat-riwayat hadis yang merekam interaksi sosial pada masa tersebut adalah Nabi Muhammad SAW menjatuhkan hukuman atau menyerang umat beragama lain dikarenakan perilaku mereka yang tidak menaati serta membangkang, bukan semata-mata karena keyakinan yang mereka anut.]